2021
DOI: 10.3390/molecules26040826
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acylguanidines as Bioinspired Catalysts for the Asymmetric Aldol Reaction

Abstract: The binding and stabilizing effect of arginine residues in certain aldolases served as inspiring source for the development of a family of amino acylguanidine organocatalysts. Screening and optimization led to identify the threonine derivative as the most suitable catalyst for the asymmetric aldol addition of hydroxyacetone, affording the syn diastereomer in high ee. In contrast, the proline derivative yielded the anti diasteromer. MMFF models suggest the presence of an extensive hydrogen bonding network betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Asymmetric organocatalysis has become an important area of research in recent years for the preparation of chiral products, being an efficient alternative to enantioselective metal-based catalysis [ 1 , 2 , 3 ]. Since List and Barbas III reported the direct aldol reaction catalyzed by l -proline [ 4 , 5 ], a variety of different organocatalysts have been evaluated for this reaction, but l -proline derivatives still represent some of the best catalysts in this regard [ 6 , 7 ] and have been used successfully in a variety of other reactions [ 8 ]. The aldol reaction continues to be a key carbon–carbon bond-forming reaction, allowing the preparation of enantiomerically enriched β -hydroxy ketones, which are important building blocks for the synthesis of structurally complex molecules with biological activity, and numerous efforts are devoted to improving both yields and stereoselectivities for this reaction [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric organocatalysis has become an important area of research in recent years for the preparation of chiral products, being an efficient alternative to enantioselective metal-based catalysis [ 1 , 2 , 3 ]. Since List and Barbas III reported the direct aldol reaction catalyzed by l -proline [ 4 , 5 ], a variety of different organocatalysts have been evaluated for this reaction, but l -proline derivatives still represent some of the best catalysts in this regard [ 6 , 7 ] and have been used successfully in a variety of other reactions [ 8 ]. The aldol reaction continues to be a key carbon–carbon bond-forming reaction, allowing the preparation of enantiomerically enriched β -hydroxy ketones, which are important building blocks for the synthesis of structurally complex molecules with biological activity, and numerous efforts are devoted to improving both yields and stereoselectivities for this reaction [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“… 15 In particular, we are interested in organocatalyzed aldol reactions under bifunctional enamine/hydrogen bonding activation. 16 20 Pioneering work by Meggers and co-workers showed that it is possible to catalyze an asymmetric α-amination reaction in an enamine/hydrogen bonding organocatalytic fashion by making use of an octahedral chiral-at-metal iridium complex. 21 …”
mentioning
confidence: 99%
“…Many different reaction types can be catalyzed by such an approach, as the asymmetric aldol reaction is a fundamental C–C bond-forming protocol essential for increasing molecular complexity in organic synthesis . In particular, we are interested in organocatalyzed aldol reactions under bifunctional enamine/hydrogen bonding activation. Pioneering work by Meggers and co-workers showed that it is possible to catalyze an asymmetric α-amination reaction in an enamine/hydrogen bonding organocatalytic fashion by making use of an octahedral chiral-at-metal iridium complex …”
mentioning
confidence: 99%